More competitive than you think? Pricing and location of processing firms in agricultural markets - Marten Graubner; Richard J. Sexton (American Journal of Agricultural Economics, 2023)
The spatial distribution of production is a defining characteristic of agriculture, and the location choice in geographic space and the spatial pricing policies adopted by agricultural processing/packing firms are key determinants of the competitiveness and efficiency of agricultural product procurement markets. Spatially distributed buying firms in the presence of costly transportation of farm products creates natural oligopsony procurement markets. Although several studies have contributed to our understanding of price and output determination and the distribution of welfare in these markets, all are limited in that they address buying firms' locations or their choices of spatial pricing strategy in isolation, holding the other factor fixed, even though both would be chosen jointly in reality to comprise a firm's product-procurement strategy. Here we overcome this limitation by using computational methods (including genetic algorithms) to study duopsony firms' joint choices of location and pricing policy. Our results differ considerably from those presented in prior literature. In general, we find that, when buyers have the flexibility to jointly choose their locations and pricing strategies, market outcomes are much more competitive and locations more efficient in terms of cost minimization than has been predicted by prior studies viewing location choice or pricing strategy in isolation.
Keywords: Q13; L13; R32; C63; C72; 330; genetic algorithm; oligopsony; price discrimination; spatial competition